Uslub Al-Istifham At-Tarbawiy Fi Surat Al-Ghasyiyah - Moh Nasrudin; Syarifatun Nadia (Arabic Education Program IAIN Pekalongan, 2016)
Qur'an is revealed in a different language style with the previous books. Everyone must have deep knowledge of rhetoric, especially semantics, to understand it. Qur'an uses rhetoric in many verses to explain some crucial issues related to education, such as teaching method which stated in Al-Ghashiyah. The objective of this research is to find out the kind of Istifham which contained in Al-Ghashiyah, the meaning of a query tool in Al-Ghashiyah, and the correlation between Al-Ghashiyah containing istifham with Islamic education. This research uses qualitative approach, with descriptive and inductive analysis method. The research result shows that there are three adawatul istifham in Al-Ghashiyah, they are: